EVALUATION OF THE TREATMENT OF FRACTURES OF THE PROXIMAL HUMERUS - CAMARA Abdoulaye, BALDE Abdoul Karim, CAMARA Nouhou Mangué, CAMARA Fatoumata, DIALLO Mamadou Moustapha, BARRY Alhassane, DIALLO Alpha Mamadou Fella, CAMARA Ibrahima Marie, KOULIBALY Mamadou, CISSE Watta, YOULA Mohamed, LAMAH Léopold (International Journal of Research Science and Management, 2023)
BACKGROUND: Fractures of the proximal humerus pose a public health problem. OBJECTIVES: The objective was to evaluate the results of different methods of treatment of proximal humerus fractures PATIENTS AND METHODS A prospective, single-center study, from January 2018 to December 2020, involving 14 patients received for proximal humerus fractures, treated, followed and evaluated. The treatment was orthopedic and surgical. After a six-month follow-up, our patients were evaluated according to the Constant-Murley score. RESULTS We collected 14 patients including 12 men (85.71%) and 2 women (14.29%), with a sex ratio of 6. The average age was 46.5 years with the extremes of 18 years and 85 years. The circumstances of occurrence were dominated by road traffic accidents with 10 cases (71.43%). All our patients were right-handed and we found 8 cases of left-sided involvement (57.14%). Subtuberosity fractures were the most encountered with 8 cases (57.14%). We carried out 7 cases (50%) of orthopedic treatment: 6 cases by Mayo-clinic and one case by Dujarier. Surgical treatment was carried out in 7 patients (50%): 4 cases by pinning and 2 cases by screwed plate and one case by staple. We recorded 5 cases of shoulder stiffness (35.71%). At six months follow-up, our results were excellent and good in 12 cases (85.71%). CONCLUSION Fractures of the proximal humerus are increasing and treatment depends on the schools. The complication to fear is shoulder stiffness.